Gaza And The Failure Of R2p: Unveiling Systemic Challenges In International Law And Geopolitics - Malahayati Rahman; Adwani Adwani; Suhaidi Suhaidi; Laila M. Rasyid (Universiti Sains Islam Malaysia, 2026)
The Responsibility to Protect (R2P) is an international commitment aimed at preventing humanitarian catastrophes. Nevertheless, in contrast to this admirable objective, the execution of R2P in Gaza reveals a situation that is quite depressing. The ongoing humanitarian crisis in the region, marked by unacceptable violence,  raises profound questions about the international community’s failure to effectively implement R2P. This study analyzes the gap between the theoretical concept of R2P, its practical application, and the geopolitical complexities in Gaza. Although many studies have discussed the obstacles to implementing R2P, only a few have reviewed in depth how this principle failed to be implemented in Gaza. It cannot be separated from various global political interests and weaknesses in international law and institutions. Although many studies have discussed the obstacles to implementing R2P, only a few have reviewed in depth how this principle failed to be implemented in Gaza. It cannot be separated from various global political interests and weaknesses in international law and institutions. This paper conducts a qualitative analysis of key international law documents, such as UN resolutions and humanitarian agency reports, as well as relevant literature and case studies. The results of this study reveal the systemic weaknesses of international law against global political factors, such as the influence of the power of major powers, the use of veto rights in the Security Council, and very inadequate law enforcement mechanisms. These findings demonstrate the failure of the international community to protect the lives of Gaza’s civilians. The study calls for reforms in international governance to ensure that R2P can serve as a real instrument to protect the population of Gaza.